A Case of Consanguinity - Carla Brown MD; Paige Jones-Brooks BS; Gwenevere White MD; Zackary Shearer MD; Megan Baber DO (SAGE Publishing, 2022)
A newborn of unknown gestational age and unknown chronological age was admitted to the neonatal intensive care unit after presenting to the emergency department for evaluation and concern for neglect. The infant was found at home by authorities with no adult caretaker. As part of routine newborn care, this infant was noted to have an abnormal newborn metabolic screen. Subsequent genetic testing confirmed an inborn error of metabolism. When family and social history became available, it was determined that the mother and putative father were genetically related. This case report discusses newborn metabolic screening and inborn errors of metabolism and their relationship to consanguinity.